HALYCH TRAGEDY OF THЕ IHOR DYNASTY - KNYSH, Yaroslav (Halych. Scientific work collection, 2017)
Basing on the study of a wide range of mainly narrative sources, the reasons of appearance of the non/existent Prince Rostyslav Ihorevych in some copies of Halych-Volhynian Chronicle are examined. It is ascertained that Roman Ihorevych together with his brother Sviatoslav, the wife of the latter Yaroslava, and their two children were executed by the citizens of Halych in September 1211.